2020
DOI: 10.1371/journal.pone.0233226
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported physical functioning and quality of life after pelvic ring injury: A systematic review of the literature

Abstract: Background Pelvic ring injuries are one of the most serious traumatic injuries with large consequences for the patients’ daily life. During recent years, the importance of the patients’ perception of their functioning and quality of life following injury has increasingly received attention. This systematic review reports on self-reported physical functioning and quality of life after all types of pelvic ring injuries. Methods The online databases MEDLINE-PubMed and Ovid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 67 publications
(238 reference statements)
0
22
0
1
Order By: Relevance
“…Some studies used the Harris Hip score [30,38,46], whereas others used the Merle d'Aubigné score [31,32,34]. Both instruments are, however, not designed and validated for evaluating the functional outcome of acetabular fractures [51]. Comparing results between studies is difficult due to the limited number of studies reporting on the functional outcome and usage of different measurement methods.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies used the Harris Hip score [30,38,46], whereas others used the Merle d'Aubigné score [31,32,34]. Both instruments are, however, not designed and validated for evaluating the functional outcome of acetabular fractures [51]. Comparing results between studies is difficult due to the limited number of studies reporting on the functional outcome and usage of different measurement methods.…”
Section: Discussionmentioning
confidence: 99%
“…A further challenge we face when interpreting current literature on management of outcomes is related to the broad variety of PROMs used in studies, particularly global health measures such as the SF-36, ODI, EQ-5D and Short Musculoskeletal Function Assessment which are not disease-specific as well as limiting translation and comparison of study findings, particularly where identical questionnaires were reported on differently [ 113 , 114 ]. PROMs related to the pelvis exist, such as the Pelvic Girdle Questionnaire, Majeed, Iowa and Orlando scores [ 115 , 116 , 117 , 118 ].…”
Section: Discussionmentioning
confidence: 99%
“…For pregnancy-related PGP, we would advise the use of the Pelvic Girdle Questionnaire as it is well-validated as previously discussed. For other causes of PGP we advise the use of validated global measures such as the VAS, EQ-5D and SF-36 or ODI, which can be compared to population norms, as the application of pelvic-specific outcomes for this population require further assessment [ 114 , 128 , 129 ].…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that 3D assisted surgery could have an effect on these measures, which is the rationale to choose these outcome measures. Moreover, these are widely used for assessing pelvic ring surgery related to patient outcomes [ 9 , 10 , 11 ]. Except for case studies with N < 10 and conference abstracts, all study designs were accepted for inclusion.…”
Section: Methodsmentioning
confidence: 99%